2008
DOI: 10.1016/j.neuroimage.2008.04.267
|View full text |Cite
|
Sign up to set email alerts
|

Chronic vagus nerve stimulation for treatment-resistant depression decreases resting ventromedial prefrontal glucose metabolism

Abstract: Vagus nerve stimulation (VNS) is used as an adjunctive therapy for treatment-resistant depression (TRD). Its mechanism of action is not fully understood. Longitudinal measurement of changes in brain metabolism associated with VNS can provide insights into this new treatment modality. Eight severely depressed outpatients who were highly treatment-resistant underwent electrical stimulation of the left vagus nerve for approximately one year. The main outcome measures were resting regional brain glucose uptake mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 77 publications
2
57
1
4
Order By: Relevance
“…Connectomic diffusion tensor imaging studies also found alterations in sgACC connectivity (Korgaonkar et al, 2014). Deep brain stimulation targeting the sgACC resulted in robust relief from depressive symptoms (Mayberg et al, 2005), and vagus nerve stimulation (Pardo et al, 2008) and antidepressant treatment also normalized sgACC metabolism (Drevets et al, 2002a; Kennedy et al, 2007). Since our group IC map did not contain an sgACC node, we view this group difference as somewhat analogous to group differences in inter-network connectivity, although sgACC is visible in the unthresholded maps shown in Figure 2 B and C.…”
Section: Discussionmentioning
confidence: 99%
“…Connectomic diffusion tensor imaging studies also found alterations in sgACC connectivity (Korgaonkar et al, 2014). Deep brain stimulation targeting the sgACC resulted in robust relief from depressive symptoms (Mayberg et al, 2005), and vagus nerve stimulation (Pardo et al, 2008) and antidepressant treatment also normalized sgACC metabolism (Drevets et al, 2002a; Kennedy et al, 2007). Since our group IC map did not contain an sgACC node, we view this group difference as somewhat analogous to group differences in inter-network connectivity, although sgACC is visible in the unthresholded maps shown in Figure 2 B and C.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, she was implanted with a VNS device (Model 102, Cyberonics, Houston, Texas, USA). Because of reports that the effects of VNS may take many months with brain metabolic changes evolving even beyond 1 year,1 2 she was advised that major antidepressant effects from VNS might take 1 to 2 years. She would need to continue intensive psychiatric management.…”
Section: Case Presentationmentioning
confidence: 99%
“…Adjunctive vagus nerve stimulation (VNS) is indicated for treatment-resistant major depression or bipolar disorder, when either the patient cannot tolerate conventional treatments, or when unresponsive to medications or convulsive seizure therapy. It has become clear that VNS can take a long time to improve mood (eg, 1 year or more1 2). However, little is known about what happens to mood-disordered patients in remission who stop VNS treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Across studies of chronic antidepressant treatment using commonly prescribed medications, prefrontal cortical changes are the most consistently reported, with normalization of frontal cortex overactivity and underactivity both described (62,(70)(71)(72). Additionally, changes are also seen in limbic and subcortical regions, including the subgenual cingulate, amygdala, hippocampus, posterior cingulate cortex, and insula, with decreased activity most commonly observed (70,71,(74)(75)(76)(77). The time course of these medication effects and differences between responders and nonresponders have provided additional localizing clues as to critical brain changes mediating depression remission.…”
Section: Brain Targets Of Antidepressant Treatmentsmentioning
confidence: 99%